Cognitive affordances in sustainable urbanism: contributions of space syntax and spatial cognition. Issue 4 (3rd July 2016) - Marcus, Lars; Giusti, Matteo; Barthel, Stephan
Abstract: Post-industrial societies impose new ecological challenges on urbanism. However, it is argued here that most approaches to sustainable urbanism still share the conception of the humans-environment relations that characterized modernism. The paper finds support in recent knowledge developments in social-ecological sustainability, spatial analysis and cognitive science to initiate a dialogue for an alternative framework. Urban form engages humans not only through physical activities, but also mentally through opportunities for learning and creation of meaning, thereby both reinforcing and impeding behaviours on a cognitive level. Against this background, it is proposed that what in cognition studies is termed 'cognitive affordances' could form the core of a new epistemological framework of the human-environment relation in sustainable urbanism.